2020
DOI: 10.3390/pr8030343
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Bio-Template Tubular MCo2O4 (M = Cr, Mn, Ni) Microstructure and Its Electrochemical Performance in Aqueous Electrolyte

Abstract: In this project, we present a comparative study of the electrochemical performance for tubular MCo2O4 (M = Cr, Mn, Ni) microstructures prepared using cotton fiber as a bio-template. Crystal structure, surface properties, morphology, and electrochemical properties of MCo2O4 are characterized using X-ray diffraction (XRD), gas adsorption, scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy (FTIR), cyclic voltammetry (CV), and galvanostatic charge-discharge cycling (GCD). The electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…The positive shift in the oxidation peak and the negative shift in the reduction peak potential show that the electrode materials have low resistance and have strong electrochemical reversibility [27]. The specific capacitance was calculated from CV curves using the Equation below [29,50,51]:…”
Section: Electrocapacitive Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The positive shift in the oxidation peak and the negative shift in the reduction peak potential show that the electrode materials have low resistance and have strong electrochemical reversibility [27]. The specific capacitance was calculated from CV curves using the Equation below [29,50,51]:…”
Section: Electrocapacitive Studymentioning
confidence: 99%
“…As a result, the electrode material offers rich redox sites to enhance electrochemical performance. Furthermore, while several supercapacitors and water splitting studies used various nickel-doped cobalt oxide morphologies [27][28][29][30][31], a few studies reported using Fe-doped cobalt oxide materials to perform the hydrogen oxidation reaction (HER) [20,22,32].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5f also indicates that, at a higher scan rate > 100 mV/s, the ion diffusion is limited to the surface of the active material of the electrode, i.e., EDLC dominates the pseudocapacitor, and diffusion of OH − ions can adhere only to the outer layer of the nanostructure, which contributes less to the electrochemical capacitive behavior [66]. On the other hand, the Faradaic redox reaction dominates at scan < 100 mV/s due to more effective usage of the working electrode's active material [67]. Moreover, the diffusion of OHions can easily penetrate deep into the nanostructure's interlayer, which leads to adsorption of more ions and hence ends up with higher specific capacitance [68].…”
Section: Resultsmentioning
confidence: 99%
“…Common examples are rechargeable batteries like Li-ion or redox flow batteries. In this special issue, two less discussed options are described, a so-called acid-base flow battery [5] and supercapacitors [6]. An acid-base flow battery is proposed by Xia et al [5].…”
Section: Electrolysis Processes For Intermediate Energy Storage In El...mentioning
confidence: 99%
“…In this special issue, development of novel electrode material for supercapacitor application based on pseudocapacitance is discussed. Guragain et al [6] developed a large-surface-area MCO 2 O 4 material in which a tubular microstructure leads to a noticeable pseudocapacitive property with the excellent specific capacitance value exceeding 407.2 F/g at 2 mV/s scan rate. In addition, a Coulombic efficiency ~100% and excellent cycling stability with 100% capacitance retention was noted even after 5000 cycles.…”
Section: Electrolysis Processes For Intermediate Energy Storage In El...mentioning
confidence: 99%